Interactive Learning Media based on Google Sites Assisted by Wordwall on Social Science Learning regarding Economic Activities - Lestari, Berliana Dwi; Fathurrahman, Moh.; Putra, Galih Mahardika Christian (Belantika Pendidikan, 2024)
Abstract: This study aims to develop and test how effective and feasible interactive learning media based on Google Sites assisted by Wordwall is on the content of the subject matter of economic activities of science and natural sciences.This study uses the Borg Gall model for research and development (RD).Data collection techniques use test and non-test techniques through pretest, posttest, interview, observation, and questionnaire activities.The results of the study showed that the assessment of material experts was 93.3 percent, media experts 98.3 percent, small class trials 91.1 percent, large class trials 93.08 percent, and teacher responses 100 percent.The N-gain results showed an increase in student learning outcomes in pretest and posttest scores.This shows that interactive learning media based on Google Sites assisted by Wordwall is practical and effective in learning the subject matter of economic activities of science and natural sciences in grade V.Abstrak: Penelitian ini bertujuan untuk mengembangkan dan menguji seberapa efektif dan layaknya media pembelajaran interaktif berbasis Google Sites berbantuan Wordwall pada muatan materi pelajaran IPAS kegiatan ekonomi. Penelitian ini menggunakan model Borg Gall untuk penelitian dan pengembangan (RD). Teknik pengumpulan data menggunakan teknik tes dan non tes melalui kegiatan pretest, posttest, wawancara, observasi, dan angket. Hasil penelitian menunjukkan penilaian dari ahli materi 93,3 persen, ahli media 98,3 persen, uji coba kelas kecil 91,1 persen, uji coba kelas besar 93,08 persen, dan respon guru 100 persen. Hasil N-gain menunjukkan adanya peningkatan hasil belajar siswa pada nilai pretest dan posttest. Hal ini menunjukkan bahwa media pembelajaran interaktif berbasis Google Sites berbantuan Wordwall praktis dan efektif dalam pembelajaran materi IPAS kegiatan ekonomi di kelas V.